2021
DOI: 10.1101/2021.08.27.457910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Basis for CPC-Sgo1 Interaction: Implications for Centromere Localisation and Function of the CPC

Abstract: The Chromosomal Passenger Complex (CPC; consisting of Borealin, Survivin, INCENP and Aurora B kinase) and Shugoshin 1 (Sgo1) are key regulators of chromosome bi-orientation, a process essential for error-free chromosome segregation. Their functions rely on their ability to associate with centromeres. Two histone phosphorylations, histone H3 Thr3 (H3T3ph; directly recognised by Survivin) and histone H2A Thr120 (H2AT120ph; indirectly recognised via Sgo1), together with CPC′s intrinsic ability to bind nucleosome,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It has been recently proposed that such well-confined concentration of CPC molecules may be important for the precise regulation of SAC signaling (Liang et al, 2020), although another study diverges on this matter (Hadders, 2020). On the other hand, in higher eukaryotes, the maintenance of normal levels of centromeric AURORA B is regarded as crucial to regulate KT-MT error correction and prevent chromosome mis-segregation Hadders, 2020;Liang et al, 2020;Abad et al, 2021). Whether each CPC pool controls specific players involved in error correction, as suggested by the ability of individual phospho-histone marks to ensure faithful chromosome segregation, remains to be determined.…”
Section: Aurora B Centromere/kt Localizationmentioning
confidence: 99%
“…It has been recently proposed that such well-confined concentration of CPC molecules may be important for the precise regulation of SAC signaling (Liang et al, 2020), although another study diverges on this matter (Hadders, 2020). On the other hand, in higher eukaryotes, the maintenance of normal levels of centromeric AURORA B is regarded as crucial to regulate KT-MT error correction and prevent chromosome mis-segregation Hadders, 2020;Liang et al, 2020;Abad et al, 2021). Whether each CPC pool controls specific players involved in error correction, as suggested by the ability of individual phospho-histone marks to ensure faithful chromosome segregation, remains to be determined.…”
Section: Aurora B Centromere/kt Localizationmentioning
confidence: 99%
“…On the other hand, Survivin binds via its Baculovirus IAP Repeat (BIR) domain to phosphorylated threonine 3 in the tail of histone H3 (H3T3 ph ) that becomes phosphorylated by the kinase Haspin ( 10 12 ). In addition, a recent study showed that Survivin is also able to bind Shugoshin at its N terminus, which structurally resembles the phosphorylated H3 tail ( 13 ). Since both interactions involve the same site of Survivin’s BIR domain, they are considered mutually exclusive in accordance with the model of two spatially distinct CPC pools: a Bub1-dependent kinetochore-proximal centromere pool, involving interactions of Survivin and Borealin with Shugoshin, and a Haspin-dependent inner centromere pool entailing the H3T3 ph Survivin contact ( 14 16 ).…”
mentioning
confidence: 99%